THE EFFECT OF ETHNOSCIENCE INTEGRATED PHENOMENON-BASED LEARNING ON STUDENTS’ SCIENTIFIC LITERACY ON TEMPERATURE, HEAT AND EXPANSION MATERIAL - Damanik, Nora; Simajuntak, Mariati Purnama (Department of Science Education, 2025)
This study aims to determine the effect of the implementation of ethnoscience integrated phenomenon-based learning on students’ scientific literacy on temperature, heat and expansion material. This type of research is a quasi experiment with two-group pretest-posttest design. The population of this study was all grade VII students of SMP Negeri 18 Medan consisting of 352 students. The research sample was taken by simple random sampling technique consisting of two classes, namely class VII-1 as an experimental class and class VII-5 as a control class, each class consisting of 32 students. The research instrument is a multiple-choice test with four options to measure scientific literacy. Data analysis using independent sample t-test and normalized-gain tests (N-gain). Based on the result of the independent sample t-test, it was found that the sig. value is 0.00 which is less than 0.05. The percentage increase in N-gain in scientific literacy in the experimental class was 74% (high category) and in the control class was 41% (medium category). Based on statistical data, it can be concluded that there is an effect of the application of ethnoscience integrated phenomenon-based learning on students' scientific literacy skill on temperature, heat and expansion material.